The Effect of the Communicative Language Teaching Method Used by Reminder Board Media - Ana Achoita; Siska Cahya Febriyanti (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
The purpose of this study is to determine the application, the mastery of vocabulary in Arabic learning, to find out how much influence the use of the Communicative language teaching method assisted by reminder board media on the mastery of Arabic vocabulary in elementary madrasas. This study uses a quantitative approach with a Nonequivalent Control Group Design. The study population was all 39 students of grade 1 of MI Al-Hidayah Gesikharjo Tuban. This study used samples from two classes, namely class 1 A and class 1 B, with a simple lottery sampling technique to determine the experimental class and the control class. Data collection instruments were observation, pretest and posttest tests, and documentation. Data analysis was carried out descriptively and inferentially using the t-test. Based on the results of the analysis using paired sample t-test with the help of SPSS 21 program In the experimental group obtained a Sig. (2-tailed) value of 0.00 <0.05 then Ha is accepted and H0 is rejected, while the results of the analysis using paired sample t-test in the control group got a Sig. (2-tailed) value of 0.26> 0.05 then H0 is accepted Ha is rejected. This in this researcher there is a significant difference between the experimental group using the communicative language teaching method assisted by the reminder board media in class I MI AL-HIDAYAH. In the data obtained through the results of the analysis using the independent sample t-test using the SPSS 21 program obtained a Sig. (2-tailed) value of 0.00 <0.05 then H0 is rejected and Ha is accepted. So it can be concluded that there is a difference in the post-test scores of the experimental group and also the control group in class I MI AL-HIDAYAH Gesikharjo students.